Proteomics Unravels Emodin Causes Liver Oxidative Damage Elicited by Mitochondrial Dysfunction - Zhang, Yinhuan; Yang, Xiaowei; Jia, Zhixin; Liu, Jie; Yan, Xiaoning; Dai, Yihang; Xiao, Hongbin (Frontiers in Pharmacology, 2020)
Emodin is one of the main active compounds of many Chinese traditional herbs. Due to its potential toxic effects on livers, the possible injury mechanism is needed to be explored. In present study, we investigated liver injury mechanisms of emodin on rats using a proteomics approach. Firstly, 4530 proteins were identified from the liver of rats treated with emodin by label free proteomics. And among them 892 were differentially expressed and down-regulated. Bioinformatics analysis showed proteins interfered by emodin were involved in redox biological process, mitochondrial fatty acid β-oxidation, citric acid cycle and oxidative phosphorylation. Proteomic data were confirmed by western blot. The decrease in maximal respiration, ATP production, spare respiratory capacity and coupling efficiency and increase in proton leakage were detected by seahorse XFe 24 analyzer, which confirmed the damage of mitochondrial function. The down-regulated expressions in antioxidant proteins were verified by western blot and the increase of ROS levels were detected in emodin group, which showed emodin interfered with redox homeostasis in livers. Molecular docking revealed that the main targets of emodin might be acadvl and complex IV. Generally, emodin could induce oxidative damage of livers by directly targeting to acadvl /complex IV and inhibiting fatty acid β-oxidation, citric acid cycle, oxidative phosphorylation taken place in mitochondria.